The Extent of Disclosure of Different Components of Disclosure Index: A Study on Commercial Banks in Bangladesh - Neogy, Taposh Kumar; Ahmed, Alim Al Ayub (Global Disclosure of Economics and Business, 2015)
This discussion highlights the disclosure score of different components of disclosure index of the selected state-owned commercial banks in Bangladesh. The annual reports of the selected commercial banks were analyzed to determine the extent of disclosure score of different components of disclosure index which contained the items of information included in the disclosure index of the selected commercial banks during the period under study. An index of disclosure has constructed less than seven heading to measure the extent of disclosure score of different components of disclosure index such as company profile items, corporate structure items, accounting policy items, balances sheet assets items, balance sheet liabilities items, income statement debit items and income statement credit items. This study shows that the disclosure score of different components of disclosure index is satisfactory and there was significant and non significant difference in disclosure score of different components of disclosure index between the selected state-owned commercial banks in different years.